2022
DOI: 10.1007/s11920-022-01389-2
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up Mental Healthcare for Perinatal Populations: Is Telemedicine the Answer?

Abstract: Purpose of Review Telemedicine has transformed our ability to access and offer mental healthcare. There remain key questions to facilitate scalable, patient-centered solutions for perinatal mental health. We critically evaluate the recent literature and propose potential future directions. Recent Findings The current literature highlights the promise of telemedicine in the prevention and treatment of perinatal depression, including the preference for and the potential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…There was no difference in rates of perinatal or postpartum depression between groups, though rates of depression were lower than predicted (< 3%, whereas a 5% rate was predicted) in both groups, which suggests the study may have been underpowered to detect a difference [45•]. This (i.e., study size) reflects one of several ongoing issues in the evaluation of telemedicine and perinatal mental health, in addition to concerns surrounding patient acceptability of remote management and how to account appropriately for comorbid trauma and substance use in patients with perinatal mood disorders [46].…”
Section: Postpartum Carementioning
confidence: 99%
“…There was no difference in rates of perinatal or postpartum depression between groups, though rates of depression were lower than predicted (< 3%, whereas a 5% rate was predicted) in both groups, which suggests the study may have been underpowered to detect a difference [45•]. This (i.e., study size) reflects one of several ongoing issues in the evaluation of telemedicine and perinatal mental health, in addition to concerns surrounding patient acceptability of remote management and how to account appropriately for comorbid trauma and substance use in patients with perinatal mood disorders [46].…”
Section: Postpartum Carementioning
confidence: 99%
“…[45][46] ■ Conclusion Given shortages of mental health care providers, stigma associated with mental health treatment, and long referral times, health policymakers are calling for colocated mental health services to be provided where individuals are receiving prenatal care. [47][48][49][50][51][52] Studies have demonstrated that CBT is an eff ective intervention for improving mental health in Black and Hispanic pregnant people, but when CBT is provided separately from prenatal care, it can be burdensome and difficult to access. 52 Work is ongoing to identify culturally acceptable, nonburdensome ways to incorporate CBT and other interventions into prenatal care.…”
Section: Implications For Practicementioning
confidence: 99%
“…To the best of our knowledge, no intervention study has been conducted on the effectiveness of mHealth consultation services in preventing PPD [ 30 , 31 ]. A recent review has called for a large randomized controlled trial investigating mHealth interventions among perinatal women [ 32 ]. We hypothesized that providing mHealth services offering free and unlimited opportunities for consultation with maternity and childcare professionals would have positive effects on maternal mental health by reducing the aforementioned healthcare access barriers, resolving perinatal concerns, and increasing benefits, even in settings where universal face-to-face perinatal mental care is available.…”
Section: Introductionmentioning
confidence: 99%